Biodegradable scaffold: integration of polylactic acid, hydroxyapatite, and graphene oxide via FDM 3D printing - André da Silva Siqueira; Natália Ferreira Braga; Pablo Andrés Riveros Muñoz; Lucas Freitas de Freitas; Aryel Heitor Ferreira; Guilhermino Jose Macêdo Fechine (eXPRESS Polymer Letters, 2024)
Extensive research and practical applications have been conducted within the biomaterials domain, focusing on polylactic acid (PLA) based composite. These composites have been explored for their favorable attributes, such as excellent processability, biodegradability, and bioactivity properties, but still lack mechanical properties. In this work, PLA-based nanocomposites were prepared by incorporating hydroxyapatite (HA) and graphene oxide (GO) via melt mixing (extruder). Filaments were obtained to develop scaffolds through 3D printing, utilizing the fused deposition method (FDM). The GO was produced using Hummer’s method and characterized by X-ray diffraction (XRD), thermogravimetric analysis (TGA), and Raman Spectroscopy. The composites were analyzed using Fourier-transform infrared spectroscopy (FTIR), molecular weight, contact angle measurements, and thermal, mechanical, and rheological analysis. Adding only 0.05 wt% of GO to both PLA and PLA/HA resulted in enhancements in mechanical properties, particularly tensile strength, and significantly modified the surface properties of the materials studied. Specifically, formulation involving PLA/HA/GO was the only one to exhibit rheological properties compatible with the scaffold production process via FDM. These specific formulations were also investigated regarding cytotoxicity, and the presence of GO induces good cytocompatibility in mouse osteoblast cells (MC3T3). These results suggest that FDM technology can be used to fabricate higher-performance (mechanical and biological) scaffolds for tissue engineering.